THE ROLE OF MATHEMATICS IN THE DEVELOPMENT OF STUDENTS' THINKING ABILITY - Sattorov Muzaffarjon Tolipovich (Zeta Repository, 2023)
This article has discussed in detail the development of logical thinking in secondary school students, the development of independent thinking, and the principlens of logic science.